Tolerance to difference as key part of students’ intercultural communication competence - Lukianets, Halyna; Lukianets, Tetiana (My University, 2024)
This paper aims at conducting conceptual analyses of tolerance term in order to specifying its meaning in education context; additionally, the paper intends to determine the level of tolerance and outline the necessity of its development among tertiary education students during foreign language classes as an integral part of overall Intercultural Communication Competence. Herein Intercultural Communication Competence refers to the ability to conduct effective communication in various cultural contexts with people from different cultural backgrounds both within the country and outside its boundaries. ICC strives to achieve a significant improvement of cultural awareness and cultural sensitivity in order to ensure successful communication and increase the mobility of students and young professionals in the world, especially those majoring in Hospitality and Tourism, and Physical Education. In other words, ICC involves two mutually connected states of knowing oneself and knowing others, which appear as a result of long-lasting process of culture exchange in and outside classroom

Ця стаття спрямована на проведення концептуального аналізу терміну толерантність для уточнення його значення в освітньому контексті. Крім того, стаття має на меті визначити рівень толерантності та окреслити необхідність його розвитку серед здобувачів вищої освіти під час занять іноземною мовою як невід’ємної частини загальної міжкультурної комунікаційної компетентності. Міжкультурна комунікативна компетенція (МКК) стосується здатності вести ефективне спілкування в різних культурних контекстах з людьми різного культурного походження як усередині країни, так і за її межами. МКК сприяє досягненню значного покращення культурної обізнаності та культурної чутливості, щоб забезпечити успішне спілкування та підвищити мобільність студентів і молодих професіоналів у світі, особливо тих, хто спеціалізується в галузі гостинності та туризму та фізичного виховання. Іншими словами, МКК включає два взаємопов'язані стани пізнання себе та пізнання інших, які виникають у результаті тривалого процесу культурного обміну в класі та поза ним
Keywords: tolerance; intercultural communicative competence; tertiary education students; cultural sensitivity; терпимість; міжкультурна комунікативна компетентність; студенти вищої освіти; культурна чутливість; кафедра іноземних мов професійного спрямування